Differential localizations of protein phosphatase 1 isoforms determine their physiological function in the heart. (5th February 2019) - Liu, Ruijie; Miller, Christian; D'Annibale, Christiana; Vo, Kimberly; Jacobs, Ashley
Abstract: Protein phosphatase 1 isoforms α, β, and γ (PP1α, PP1β, and PP1γ) are highly homologous in the catalytic domains but have distinct subcellular localizations. In this study, we utilized both primary cell culture and knockout mice to investigate the isoform-specific roles of PP1s in the heart. In both neonatal and adult cardiac myocytes, PP1β was mainly localized in the nucleus, compared to the predominant presence of PP1α and PP1γ in the cytoplasm. Adenovirus-mediated overexpression of PP1α led to decreased phosphorylation of phospholamban, which was not influenced by overexpression of either PP1β or PP1γ. Interestingly, only cardiac-specific knockout of PP1β resulted in increased HDAC7 phosphorylation, consistent with the predominant nuclear localization of PP1β. Functionally, deletion of either PP1 isoform resulted in reduced fractional shortening in aging mice, however only PP1β deletion resulted in interstitial fibrosis in mice as early as 3 weeks of age. Deletion of neither PP1 isoform had any effect on pathological cardiac hypertrophy induced by 2 weeks of pressure overload stimulation. Together, our data suggest that PP1 isoforms have differential localizations to regulate the phosphorylation of their specific substrates for the physiological function in the heart.